ダイ4ジ ソウヤ センジョウ ニオケル タイキコウ キセン ノ コウデン カンソク ケッカ ホウコク - 中村, 強; ナカムラ, ツヨシ; NAKAMURA, Tsuyoshi (国立極地研究所, 1961)
P(論文) In addition to the observation of 5577A emission in the night air-glow, made in the First, Second, and Third Expeditions, the observations of three other emissions were carried out in the Fourth Expedition along the same course of the SOYA between Tokyo and the Antarctic. The latitude dependency of the 5577A emission of oxygen atom has not particularly shown any new result to be added to the past observations on the SOYA. The general tendency of the latitude dependency of the D-line of sodium atom is that it is stronger around the equator and weaker in higher latitudes. The intensity of 6300A red-line shows a remarkable increase in low latitudes and also shows large seasonal variation. In low latitudes, daily variation of its intensity is larger than in middle latitudes. It seems that this effect is due to the vertical motion of emitting layer in low latitudes. The intensity of red-line shows a good correlation with the integrated value of product of density of both electrons and oxygen molecules in the F layer. The latitude dependency of the OH band in the near infra-red region is somewhat similar to that of 5577A line, but the seasonal effect of this band seems to be very small, and this is in agreement with the small seasonal variation observed at IGY stations. departmental bulletin paper